Analisis Komunikasi Konstruksi Citra Partai Keadilan Sejahtera Melalui Kegiatan Komunitas Senam Nusantara Pasar Kemis Kabupaten Tangerang - Rindiani, Luthfiyyah; Khairani, Aulian; Hardiyanti, Rini (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
The declining public trust in political parties compared to other state institutions has made political parties increasingly aware of the importance of building a positive image and maintaining good relationships with the public. This research focuses on the role of the Komunitas Senam Nusantara (KSN), a social community focused on physical fitness. However, their social activities go beyond just exercising; they frequently organize charity events for orphans and the underprivileged, provide free health check-ups, and conduct other social activities at no cost, in assisting the Prosperous Justice Party (PKS) in building its image. KSN, founded with the involvement of several PKS cadres, actively organizes social activities open to the public. To achieve this objective, this research employs a descriptive qualitative method to accurately depict the situation. The data indicates that PKS's electability in the most recent election has increased, although not significantly, including in the Tangerang local election. This study also highlights the importance of effective communication strategies by PKS to maximize the positive impact generated by KSN's activities.